Manfaat Media Kartu Gambar untuk Peningkatan Membaca Permulaan Anak Usia Dini: Studi Kasus TK Kristen Satu Atap Sabron Yaru Kabupaten Jayapura - Christina Anita Jeujanan; Ria Imelda Simanjuntak (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research was conducted at TK Satu Atap Sabron Sari, Kampung Sabron Sari, Sentani Barat District, Jayapura Regency, focusing on the effectiveness of using picture cards as a medium to enhance early reading skills in young children. Established on July 9, 2010, under the auspices of Yayasan Laskar Kristus, this kindergarten offers a conducive and comfortable learning environment, making it a preferred choice for many parents in the area. The study employed an observational method with a two-cycle learning approach. In Cycle I, it was found that the majority of the students were categorized as Not Yet Developed in reading ability. However, in Cycle II, following the implementation of picture cards as a learning medium, there was a significant improvement in reading skills, with an increase in the number of students achieving Developed According to Expectations and Fully Developed categories. These results indicate that the use of picture cards is an effective method to enhance early reading skills. This study underscores the importance of selecting appropriate learning media to support the learning process in early childhood, especially in the context of beginning reading skills.